2014
DOI: 10.5120/16658-6639
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ICT in Reducing Maternal and Neonatal Mortality Rate in Tanzania

Abstract: Tanzania is striving to achieve Millennium Development Goals (MDG) 4 and 5 that call for reducing Neonatal and Maternal Mortality Rate (MNMR) by 2015. In 2010, Neonatal Mortality Rate (NMR) was recorded at 51 per 1,000 live births and Maternal Mortality Rate (MMR) at 454 per 100,000 live births. Despite of the devoted efforts and significant progress, still the mortality rate needs attention and effective intervention to cut it down considerably. The capability and power of Information and Communication Techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
(4 reference statements)
1
5
0
1
Order By: Relevance
“…This is followed by "it has made me to be aware of the benefits of participating in antenatal and post-natal clinics" with mean score of ( X ¼3.38). This finding is consistent with studies by (Nyamawe and Seif, 2014;Fedha, 2014 andWest, 2014) which reported a positive impact of communication technologies on access to maternal and child care services as well as health information. Factors that militate against effective access to maternal and child health information using the communication technologies…”
Section: Women's Perception Of Impact Of Information and Communicatiosupporting
confidence: 92%
“…This is followed by "it has made me to be aware of the benefits of participating in antenatal and post-natal clinics" with mean score of ( X ¼3.38). This finding is consistent with studies by (Nyamawe and Seif, 2014;Fedha, 2014 andWest, 2014) which reported a positive impact of communication technologies on access to maternal and child care services as well as health information. Factors that militate against effective access to maternal and child health information using the communication technologies…”
Section: Women's Perception Of Impact Of Information and Communicatiosupporting
confidence: 92%
“…Not much improvement was achieved in reducing maternal morbidity and mortality (6,7). Similarly, Tanzania was not able to meet the expected MDG target until 2015 (5,8). This persistence of high levels of Maternal Mortality Ratios (MMR) have persisted despite the investment of resources to improve the quality of maternal and newborn care in the areas of training and deployment of human resources for health, construction of health facilities, and supply of medical products (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine memberikan keuntungan kepada tenaga kesehatan terutama pada kondisi dengan sumber daya rendah (Vesel et al, 2015). Pada 2013, pengembangan dan penggunaan telemedicine mampu menjadi alat pemantauan dalam menidentifikasi ancaman pada ibu dan anak sehingga dapat dilakuakan tindakan pencegahan di Daerah Singida, Tanzania (Nyamawe, 2016). Penerapan Telemedicine di Kabupaten Kupang juga dirasakan mampu meningkatkan hasil kerja bidan.Telemedicinedapat digunanakan sebagai cara untuk memantau dan mengawasi yang lebih baik dari pada cara konvensional.…”
Section: Hasil Dan Pembahasan Performance Expectancyunclassified